Electrochemical oxidation of quercetin in hydro-alcoholic solution - Timbola,Ana K. (2006)
The electrochemistry of quercetin hydro-alcoholic solutions of pH 2.2 to 9.2 was studied by cyclic voltammetry, controlled-potential electrolysis and UV-Vis spectroscopy. Cyclic voltammograms for quercetin showed three oxidation peaks and one reduction peak depending on the experimental conditions. The two-electron two-proton oxidation process at the first peak led to the formation of the corresponding ortho-quinone, which is an electrochemically active and unstable species, as evidenced by the dependence of the cyclic voltammogram profile on the applied scan rate, in agreement with the EC mechanism. Controlled-potential electrolysis yielded three products as characterized by UV-Vis spectroscopy. A reaction scheme comprising electrochemical and chemical steps was proposed for the electro-oxidation of the quercetin in hydro-alcoholic solutions on basis of experimental evidences obtained in this work and elsewhere.